Epidermal Growth Factor Promotes E6 and CCL-81 Vero Cells Proliferation Under Serum-Free Condition - Delaiah, Diena; Aswin, Ahmad; Susilowati, Helen; Wijaya, Andi Yasmin; Maulana, Firdausy Kurnia; Diyantoro, Diyantoro; Rodprasert, Watchareewan; Puspitasari, Yulianna; Dhamayanti, Yeni; Kuncorojakti, Suryo (Universitas Airlangga, 2024)
Vero cell culture as a platform for producing viral vaccines is an established and standardized process in vaccine manufacture. Generally, Vero cell culture requires media as a source of nutrition with serum supplementation to provide growth factors. However, the serum has several disadvantages including batch to batch variation and adventitious agent. Therefore, chemically defined serum-free media (SFM) are formulated by using standardized growth factors. Epidermal Growth Factor (EGF) is one of growth factors that showed adequate mitogenic support in serum-free medium system, especially in Vero cells. In this study, SFM-EGF media was compared with serum supplementation media, namely MEM 10% and MEM 5% FBS supplementation. The cell morphology was observed using an inverted microscope and their proliferation was evaluated using a MTT colorimetric-based assay. Vero E6 and Vero CCL-81 cells morphology did not show any morphological changes. Vero E6 and Vero CCL-81 proliferation in SFM-EGF media on day one to four did not show a significant difference compared to MEM 10% or MEM 5% serum supplementation media. However, the OD values of both Vero E6 and Vero CCL-81 cells given SFM-EGF media produced an average value below MEM 10% but higher than MEM 5% FBS supplementation. As such, this study proved that utilizing SFM-EGF could support the proliferation of Vero E6 and Vero CCL-81 cells.